KONSEP DIRI MASYARAKAT KEPULAUAN - Watloly, Aholiab (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2012)
Indonesian culture has a strong root in a culture of island communities. The culture, especially philosophy of the island communities is not so much revealed in studies of philosophy and culture. Therefore, this article will explore and explain philosophical values that shape the self-concept of the island communities. Epistemology is used as a formal object, while the material object is the island communities’ views and way of life. This article concludes that for the island communities, their islands are not just meant as a territorial locus, but also a cultural and personal locus because the islands have a concept of self and a sense of space and existence. Every community always identifies and conceptualizes themselves in a cosmological and socio-cultural concept. Every community has local knowledges, values, and institutions that are formed by an original natural ratio. The natural ratio grows from cosmic consciousness level to magical (religious) consciousness, and finally social consciousness. Willingness and policies are needed to build resilience and progress of the nation existence through a development of the island communities manifestly. The development of island communities must become one of important features of national development in Indonesia.